(untitled) (Bangladesh Journal of Neuroscience, 2017)
Ischemic stroke patients suffer from different complications among which nonneurological medical complications are common along with stroke related neurological complications. This observational study was aimed to find out these non-neurological common medical complications of acute ischemic stroke patients admitted in hospital in this country. This study was conducted by every day observation of acute ischemic stroke patients admitted in the hospital. Medical complications were diagnosed on the basis of clinical features and laboratory findings. In acute ischemic stroke patients, development of medical complications is more common (60%). Among them infective complications were found more than non-infective complications. Urinary tract infections (17.8%), respiratory tract infection (17.8%), mixed complications (13.3%) were found commoner than other complications. Length of hospital stay (LOHS) was prolonged in those patients who developed these complications. These complications play a vital role in outcome of the patients. Bangladesh Journal of Neuroscience 2017; Vol. 33 (1): 13-17